2021
DOI: 10.3390/cells10051135
|View full text |Cite
|
Sign up to set email alerts
|

Acid Sensing Ion Channel 2a Is Reduced in the Reduced Uterine Perfusion Pressure Mouse Model and Increases Seizure Susceptibility in Pregnant Mice

Abstract: Eclampsia is diagnosed in pregnant women who develop novel seizures. Our laboratory showed that the reduced uterine perfusion pressure (RUPP) rat model of preeclampsia displays reduced latency to drug-induced seizures. While acid sensing ion channels (ASIC1a and 3) are important for reducing seizure longevity and severity, the role of ASIC2a in mediating seizure sensitivity in pregnancy has not been investigated. We hypothesized that 1) RUPP reduces hippocampal ASIC2a, and 2) pregnant mice with reduced ASIC2a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 45 publications
(61 reference statements)
1
13
0
Order By: Relevance
“…The involvement of ASICs, including ASIC2, is observed in neuronal excitability, especially in relation to imbalances in neuronal excitation seen in seizure and epilepsy [79][80][81]. Amiloride has been shown to reduce generalized seizures induced by either pentylenetetrazole or electrical stimulation [18,82].…”
Section: Epilepsymentioning
confidence: 99%
“…The involvement of ASICs, including ASIC2, is observed in neuronal excitability, especially in relation to imbalances in neuronal excitation seen in seizure and epilepsy [79][80][81]. Amiloride has been shown to reduce generalized seizures induced by either pentylenetetrazole or electrical stimulation [18,82].…”
Section: Epilepsymentioning
confidence: 99%
“…The publicly open NIH program announcement (PA-19-034) detailing the classification and identification of 390 understudied druggable genomes was utilized to acquire the list of 261 candidate genes encoding GPCRs and ion channels. The associated literature survey was performed until 9 December 2021, with emphasis on published title words with (1) ion channels since 2017 [4,5,[9][10][11][12][13][14]16,26,27,30,33,[39][40][41][42]44,[46][47][48]53,54,59,61,[69][70][71][72][73][74][75][76][77][78][79][80], (2) ion channel blockers since 2017 [41,[81][82][83][84][85][86][87][88][89][90]…”
Section: Database Literature and Open-access Softwarementioning
confidence: 99%
“…When designing a new drug, some would rather avoid interactions with ion channel proteins, particularly due to cardiovascular safety concerns. Although several attempts have been made to target ion channels, such as K + channel blockers for autoimmune disease [34,35] and antiseizure medications [36][37][38][39][40], and antiarrhythmic treatments [41][42][43][44][45][46], targeting ion channels has resulted in a limited commercialization, as evidenced in the development of Ca 2+ channel blockers for hypertension [47,48]. Nevertheless, a pathway for therapeutic success [49] and significant progress have been achieved with drugs that target Cl − channels, such as cystic fibrosis transmembrane conductance regulator (CFTR) [50].…”
Section: Introductionmentioning
confidence: 99%
“…Both ASIC1a and ASIC3 have been shown to be important for seizure termination ( Ziemann et al, 2008 ; Cao et al, 2016 ; Cao et al, 2018 ). Interestingly, in our previous publication, we showed that pregnant ASIC2a heterozygous knockout (+/-) mice have increased seizure severity and sensitivity ( Jones-Muhammad et al, 2021 ). The molecular mechanisms underlying increased seizure sensitivity and severity in pregnant ASIC2a +/- mice are not fully known.…”
Section: Introductionmentioning
confidence: 96%
“…To date, the mechanisms that contribute to novel seizures during pregnancy are still unclear. In our previous study, we showed that the preclinical mouse model of reduced utero-placental perfusion (RUPP), which shares some of the clinical features of preeclampsia, has decreased placental and hippocampal expression of acid sensing ion channel 2a (ASIC2a) ( Jones-Muhammad et al, 2021 ). ASICs are mechano- and chemo-receptor channels with important roles in modulating seizure activity ( Liang et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%